2022
DOI: 10.3389/fnut.2022.916642
|View full text |Cite
|
Sign up to set email alerts
|

Flavor and Other Quality Traits of Tomato Cultivars Bred for Diverse Production Systems as Revealed in Organic Low-Input Management

Abstract: This study was conducted to determine the volatile organic compounds (VOCs) associated with fruit flavor in diverse tomato cultivars (salad and cocktail cultivars) under organic low-input production. For this objective, 60 cultivars deriving from very diverse breeding programs 1880–2015 were evaluated in 2015, and a subset of 20 cultivars was selected for further evaluation in 2016. The diversity of instrumentally determined traits, especially for VOCs concentration and sensory properties (fruit firmness, juic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
3
2
0
Order By: Relevance
“…Apparently, these two special sensory attributes were not perceived as typical for tomatoes and might be specific to this mapping population. In agreement with Baldwin et al (2015) and Erika et al (2022), we found significant correlations between TSS and sweetness ( r = .57) and between TA and sourness ( r = .23). Although measuring TSS and TA allows breeders to select for tomato taste (Tandon et al, 2003), Colantonio et al (2022) emphasized the importance of aroma volatiles for sensory attributes by quantifying the proportion of phenotypic variance explained by sugars, acids and volatile compounds.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Apparently, these two special sensory attributes were not perceived as typical for tomatoes and might be specific to this mapping population. In agreement with Baldwin et al (2015) and Erika et al (2022), we found significant correlations between TSS and sweetness ( r = .57) and between TA and sourness ( r = .23). Although measuring TSS and TA allows breeders to select for tomato taste (Tandon et al, 2003), Colantonio et al (2022) emphasized the importance of aroma volatiles for sensory attributes by quantifying the proportion of phenotypic variance explained by sugars, acids and volatile compounds.…”
Section: Discussionsupporting
confidence: 93%
“…Flavour is not only influenced by genetics but also by environmental factors and agronomic handling (Baldwin et al, 2015;Erika et al, 2022;Klee & Tieman, 2018), as also shown by our results…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although numerous plant compounds have revealed bioactive properties, including antioxidant, anti-inflammatory, and anticancer, the combination of the tomato and the olive has several advantages: (a) none of the other “plant compounds” have the properties of tomato and olive in terms of fulfilling the criteria that we have referred to in the section “Tomato and olive eco sustainability” [ 13 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ], representing a limitation in their use as functional foods; (b) a dose-dependent effect has been demonstrated only for a limited number of plants; (c) none of the other plant compounds are known to concentrate in the prostate and to provide the complex of molecules with converging biological effects such as those summarized in Table 1 ; and (d) when dealing with aging-related prostate diseases, the WTBS is also endowed with anti-androgen receptor inhibition [ 120 ].…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Tomato, which represents the second most popular crop worldwide [ 59 ], has a high global consumption rate [ 60 ]. The fruit, characterized by extensive biodiversity [ 61 ] and chemodiversity [ 62 ], with a high average nutritional yield [ 63 ], requires timely controlled irrigation and moderate soil tillage [ 64 ]. Tomatoes accumulate low levels of environmental contaminants [ 65 ] in the fruit and are thus considered to be an “excluder plant” since they concentrate soil contaminants in the roots, stems, and shoots [ 64 ].…”
Section: Tomato and Olive Oil In Prostate Healthmentioning
confidence: 99%